Combined treatment of epi-brassinolide and NaCl enhances the main phytochemicals in Chinese kale sprouts. (15th June 2020) - Wang, Mengyu; Cai, Congxi; Lin, Jiayao; Tao, Han; Zeng, Wei; Zhang, Fen; Miao, Huiying; Sun, Bo; Wang, Qiaomei
Highlights: NaCl treatment alone or combined with eBL improved the content of glucosinolates. Combined treatment of eBL and NaCl enhanced ascorbic acid content. Combined treatment of eBL and NaCl attributed to the increase of carotenoid content. The expression of MYB transcription factors was activated by the eBL and salt stress. Abstract: The effects of individual epi -brassinolide (eBL) and NaCl, as well as their combination on contents of main phytochemicals and antioxidant capacity of Chinese kale sprouts were investigated. Our results showed that the application of 100 nM eBL decreased the contents of individual and total glucosinolates, while treatments of 160 mM NaCl both alone and combined with 100 nM eBL enhanced the glucosinolates accumulation by promoting the expression of genes involved in glucosinolate biosynthesis in Chinese kale sprouts and the combined treatment led to significantly higher content of most glucosinolate profiles. Moreover, it also elevated the contents of ascorbic acid and total carotenoids, whereas did not influence the total phenolics and antioxidant capacity. These findings indicated that the combined treatment of 100 nM eBL plus 160 mM NaCl could provide a new strategy to improve the main health promoting compounds in Chinese kale sprouts.